Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis - Lankes, Katharina; Hundorfean, Gheorghe; Harrer, Thomas; Pommer, Ansgar J.; Agaimy, Abbas; Angelovska, Irena; Tajmir-Riahi, Azadeh; Göhl, Jonas; Schuler, Gerold; Neurath, Markus; Hohenberger, Werner; Heinzerling, Lucie (OncoImmunology, 2016)
Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study developed severe immune-mediated colitis (CTCAE grade 3) with up to 18 watery stools per day starting 2 weeks after treatment initiation. After improving upon therapy with immunosuppressive treatment (high dose steroids and infliximab) combined with parenteral nutrition diarrhea again exacerbated. Additionally, the patient had asymptomatic grade 3 CTCAE amylase and lipase elevation. Colitis was monitored by weekly endoscopies and colon biopsies were analyzed histologically with CMV staining, multi-epitope ligand cartography (MELC) and qRT-PCR for inflammatory genes. In the course, CMV reactivation was detected in the colon and treated with antiviral medication in parallel to a reduction of corticosteroids. Subsequently, symptoms improved. The patient showed a complete response for 2 y now including regression of bone metastases. CMV reactivation under checkpoint inhibitor therapy in combination with immunosuppressive treatment for autoimmune side effects has to be considered in these patients and if present treated. Potentially, CMV reactivation is underdiagnosed. Treatment algorithms should include CMV diagnostics.
EVALuna2:2063

Beruflich erworbene MRSA-Besiedelung in der berufsdermatologischen Begutachtung (BK-Nr. 3101) - Erfurt-Berge, Cornelia; Schmidt, Anne; Angelovska, Irena; Mahler, Vera (Hautarzt, 2020)
Background: Person-to-person transmitted infectious diseases can cause occupational diseases (OD). These are subsumed as BK-No. 3101 in the German list of OD which applies for individuals with a considerably higher risk for infection as a consequence of their professional activity compared to the general population. Objectives: The special medical and insurance law aspects of a work-related MRSA colonization are presented using the example of an expert opinion case and an evaluation of the BK reports of suspected occupational disease (BK No. 3101) of the German Social Accident Insurance (DGUV). Patients and methods: The BK documentation of the DGUV from 2007–2012 and the patient cohort from the Department of Dermatology, University Hospital Erlangen, presenting for expert assessment from 2007–2012 were retrospectively analysed for human-to-human transmitted infectious diseases of the skin (BK-No. 3101). Results: Person-to-person transmission of infectious diseases of the skin is rare in the field of occupational dermatology. In the DGUV cohort, suspected BK-No. 3101cases amounted to 2.6% of all notified cases; recognized BK-No. 3101 cases accounted for 4.2% of all recognized cases, amongst which 9 were caused by MRSA. In contrast to a symptomatic infection, an asymptomatic MRSA colonization is not being recognized as BK-No. 3101. Bacterial superantigens can trigger atopic dermatitis (AD). In particular cases, occupationally acquired MRSA can elicit AD and may justify classification as an OD (BK-No. 3101). Conclusions: Early detection of MRSA colonization and eradication are necessary for rehabilitation. Management of skin diseases due to infectious diseases within the framework of OD is presented.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Abnormal health condition; Asymptomatic MRSA colonization; Communicable disease; Occupation diseases; Occupational disease evaluation proceedings

Occupational palmoplantar psoriasis: a clinical case series with consideration of the S1 guidelines on expert medical assessments of occupational psoriasis - Angelovska, Irena; Mahler, Vera (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
Constitutional diseases represent a challenge in the expert assessment of occupational diseases. It is necessary to distinguish professional causes from the spontaneous course of the disease. Recently, a guideline for the assessment of work-related psoriasis has been consented in Germany. We present a case series in which it was applied.129 expert assessments from the Department of dermatology University hospital Erlangen and court cases in established juridical databases were researched for cases with psoriasis and the applicability of the guideline.The guideline was applicable in the n = 6 (3.6 %) identified medical expert opinions. They were fully recognized by the workers compensation boards. The search for law sentences on work-related psoriasis in German court cases yielded a total of four sentences, in one of which the psoriasis was recognized as an occupational disease (BK 5101).In comparison with hand eczema psoriasis of the hands is rare. As has been demonstrated in our case series psoriasis as a constitutional disease may be recognized as an occupational disease (BK 5101) according to the legal system in Germany, if the influence of occupational exposure can be made sufficiently probable and other legal conditions of an occupational disease are met.
EVALuna2:19456